Simultaneous Gas Absorption and Liquid Phase Chemical Reaction - Pang, Kwok-Hing (My University, 1965)
The present apparatus was used to obtain rate data for the absorption of oxygen in a catalysed liquid phase reaction with acetaldehyde. The effects of several system parameters, namely, acetaldehyde concentration, catalyst concentration, partial pressure of oxygen and temperature on the rate of absorption were studied. An attempt was made to correlate absorption rates and product distribution with mathematical models based on the film theory and existing kinetic models proposed by Bolland and Bawn. Absorption rates predicted by these semi-empirical correlations are compared with experimental values. The differential equations involving diffusion with chemical reaction were solved on the digital computer IBM 7040 and the analog computer PACE TRlO.
Keywords: Gas Absorption; Liquid Phase; Chemical Reaction; acetaldehyde